Gurltia paralysans Infection in Domestic Cats in the State of Pernambuco, Brazil - de Melo Neto, Gabriel Barbosa; da Silva, Luis Raimundo; Alves, Rodrigo da Cruz; Olinda, Robério Gomes; Medeiros Dantas, Antônio Flávio; de Medeiros Torres, Márcia Bersane Araújo (Acta Scientiae Veterinariae, 2019)
Background: The Gurltia paralysans nematode was initially described in Chile and for many years it was believed that the disease caused by this parasite was restricted to this country. However, in Argentina, Uruguay and more recently in Brazil, among other countries, cases of Gurltiosis have been described in both domestic and wild cats. This disease is chronic and debilitating due to the progressive paralysis developed. This study aimed to describe the clinical, epidemiological and pathological aspects of G. paralysans infection in domestic cats of the Agreste region of the state of Pernambuco, Northeast Brazil. Case: Clinical, epidemiological and pathological aspects of Gurltia paralysans infection in domestic cats in the rural area of two Agreste municipalities in the state of Pernambuco, Brazil, are described. Seven farms were visited, in which 11 male and female affected felines were evaluated. Among these, euthanasia was performed in four cases, at the owners' request and due to the advanced stage of the disease. Clinical signs began with ataxia of the pelvic limbs and evolved to jumping difficulty, lateral falls, muscle atrophy, pelvic limb scarring, and paralysis at the most severe stage of the disease, which developed in a one-year period, approximately. According to the owners, the affected cats died between six months and one year after the initial clinical signs. At necropsy, there were segments of the spinal cord with extensive reddish areas in the dura, between T7 and S2, corresponding to varices. These were characterized by numerous congestive, dilated and tortuous blood vessels observed in the dorsal plane, but more pronounced in the ventral plane of the meninges. In the bladder, multifocal areas of hemorrhage were observed. Histologically, vascular lesions in veins and venules of the leptomeninges were characterized by venous varices with thrombosis, fibrosis and intravascular parasites associated with moderate, chronic non-suppurative meningoencephalomyelitis and Wallerian degeneration. Macroscopic and microscopic lesions were more pronounced in the lumbar region of the spinal cord. Discrete lesions similar to those found in the spinal cord were observed in the encephalon. Feline gurltiosis was confirmed by epidemiological, clinical and spinal cord lesions, associated with the presence of intravascular parasites in veins and venules of the leptomeninges. The identification of Gurltia paralysans was concluded due to the characteristic morphology of the parasite in the vessels. Discussion: The diagnosis of Gurltiosis can be performed by clinical-epidemiological findings and histopathological evaluation of the nervous system demonstrating the parasite inside the vessels. The parasite has affinity for the nervous tissue, especially the lumbar spinal cord, in which it can be found in the nervous parenchyma and not only in the veins as previously believed. The chronicity of the disease can be affirmed by clinical signs, secondary lesions, such as cystitis, and the evolution of the condition. The stasis of blood caused by the varicose veins favored the formation of thrombi and compression of the white matter by the parasites, which explains the clinical signs. The geographical distribution of the disease goes beyond the initially known sites. Although little is known about the pathogenesis of Gurltiosis, it is possible to affirm that domestic cats ingest the parasite from a paratenic host, which would justify the cases recorded in rural environments. It is concluded that the disease, popularly known as "derrengado" or "renga", refers to feline gurltiosis, characterized by venous varices and chronic progressive myelitis. These results demonstrate that the disease is distributed in other regions of Brazil. However, studies are necessary to describe the form of infection so that prevention measures can be investigated. Gabriel Barbosa de Melo Neto, Luis Raimundo da Silva, Rodrigo Cruz Alves, Robério Gomes Olinda, Antônio Flávio Medeiros Dantas & Márcia Bersane Araújo de Medeiros Torres